Birth Order and Delinquency: Evidence from Denmark and Florida - Sanni Breining; Joseph Doyle; David N. Figlio; Krzysztof Karbownik; Jeffrey Roth (Center for Economic Studies and ifo Institute (CESifo), 2017)
Birth order has been found to have a surprisingly large influence on educational attainment, yet much less is known about the role of birth order on delinquency outcomes such as disciplinary problems in school, juvenile delinquency, and adult crime: outcomes that carry significant negative externalities. This paper uses particularly rich datasets from Denmark and the state of Florida to examine these outcomes and explore potential mechanisms. Despite large differences in environments across the two areas, we find remarkably consistent results: in families with two or more children, second-born boys are on the order of 20 to 40 percent more likely to be disciplined in school and enter the criminal justice system compared to first-born boys even when we compare siblings. The data allow us to examine a range of potential mechanisms, and the evidence rules out differences in health at birth and the quality of schools chosen for children. We do find that parental time investment measured by time out of the labor force is higher for first-borns at ages 2-4, suggesting that the arrival of a second-born child extends early-childhood parental investments for first-borns.
Keywords: J01; 330